Royal Jelly as a Nutraceutical Natural Product with a Focus on Its Antibacterial Activity - Lilla Bagameri; Gabriela-Maria Baci; Daniel Severus Dezmirean (Pharmaceutics, 2022)
Royal jelly (RJ) is one of the most valued natural products and is known for its health-promoting properties. Due to its therapeutic effects, it has been used in medicine since antiquity. Nowadays, several studies indicate that RJ acts as a powerful antimicrobial agent. Indeed, researchers shed light on its antioxidant and anticancer activity. RJ’s biological properties are related to its bioactive compounds, such as proteins, peptides, phenolic, and fatty acids. The aim of this review is to highlight recent findings on RJ’s main bioactive compounds correlated with its health-promoting properties. The available literature suggests that these bioactive compounds can be used as an alternative approach in order to enhance human health. Moreover, throughout this paper, we underline the prominent antibacterial effect of RJ against several target bacterial strains. In addition, we briefly discuss other therapeutic activities, such as antioxidative and anticancer effects, of this outstanding natural product.